Pegmatites of the Larsemann Hills oasis, East Antarctica: new field geological and geophysical data - Ivan A. Babenko; Irina V. Talovina; Dmitrii E. Ushakov; Nikita S. Krikun (Записки Горного института, 2025)
This paper presents new data on various types of pegmatites from the Larsemann Hills oasis (Princess Elizabeth Land, East Antarctica), collected during the 70th Russian Antarctic Expedition in 2024-2025. As a result of comprehensive geological and geophysical investigations, all pegmatite occurrences in the area belonging to different stages of the Pan-African orogeny have been described, analyzed, and systematically classified in a unified context for the first time. In addition to previously known pegmatites associated with deformation stages D2-3, D4, and post-D4, a further subdivision is proposed based on mineralogical-geochemical characteristics and the content of natural radionuclides. These include borosilicate D2-3 pegmatites, rare-metal D4 pegmatites, muscovite-bearing post-D4 pegmatites, as well as two newly identified types not previously described in the region: K-feldspar D4' pegmatites and miarolitic rare-metal post-D4' pegmatites, which differ in morphology, mineralogy, and geochemical features. Special attention is given to the structural-tectonic control of pegmatite bodies, their geological setting, zoning patterns, and the results of gamma spectrometric and magnetic surveys. Pegmatitic formations containing rare typomorphic minerals – such as tourmaline, boralsilite, grandidierite, and chrysoberyl – are also examined. The results indicate a significant diversity of pegmatite formation conditions, help refine the PT parameters and timing of the initial and final stages of the Pan-African metamorphic event, and confirm the genetic link between pegmatite development and D2-D4 deformation stages. These findings contribute to the reconstruction of Early Paleozoic pegmatite-forming stages during anatectic processes in the geodynamic evolution of East Antarctica and Gondwana.